2022
DOI: 10.1038/s41598-022-14988-z
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between continuous cardiac output measured by the fourth-generation FloTrac/Vigileo system and a pulmonary artery catheter in adult liver transplantation

Abstract: In liver transplantation for end-stage liver failure, monitoring of continuous cardiac output (CCO) is used for circulatory management due to hemodynamic instability. CCO is often measured using the minimally invasive FloTrac/Vigileo system (FVS-CCO), instead of a highly invasive pulmonary artery catheter (PAC-CCO). The FVS has improved accuracy due to an updated cardiac output algorithm, but the effect of this change on the accuracy of FVS-CCO in liver transplantation is unclear. In this study, we assessed ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Here, ClearSight™ did not exhibit clinically acceptable interchangeability with PAC in terms of CO and SVR. Similarly, previous studies have also reported poor interchangeability in the CI and SVR between PAC and other less-invasive arterial pulse wave analyses during liver transplantation [ 14 , 15 , 37 ]. Patients with cirrhosis undergoing liver transplantation possess unique characteristics, such as hyperdynamic circulation and low SVR, which potentially increase the inaccuracy of arterial pulse wave analysis [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Here, ClearSight™ did not exhibit clinically acceptable interchangeability with PAC in terms of CO and SVR. Similarly, previous studies have also reported poor interchangeability in the CI and SVR between PAC and other less-invasive arterial pulse wave analyses during liver transplantation [ 14 , 15 , 37 ]. Patients with cirrhosis undergoing liver transplantation possess unique characteristics, such as hyperdynamic circulation and low SVR, which potentially increase the inaccuracy of arterial pulse wave analysis [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, previous studies have also reported poor interchangeability in the CI and SVR between PAC and other less-invasive arterial pulse wave analyses during liver transplantation [ 14 , 15 , 37 ]. Patients with cirrhosis undergoing liver transplantation possess unique characteristics, such as hyperdynamic circulation and low SVR, which potentially increase the inaccuracy of arterial pulse wave analysis [ 15 , 38 , 39 ]. Additionally, rapid changes in hemodynamic status during liver transplantation occur due to massive bleeding, manipulation of the IVC, inflammatory mediators after reperfusion of the graft, and the common use of vasoactive drugs that affect vascular compliance, thus negatively affecting the accuracy of arterial pulse wave analysis, including ClearSight™ [ 1 , 3 , 22 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Uncalibrated or internally calibrated pulse wave analysis systems lose reliability when arterial tone changes significantly. This has been confirmed with the most recent models during coronary artery bypass [21–23], liver transplantation [24], or hyperthermic intraperitoneal chemotherapy [25], that is, situations in which the arterial tone varies to a large extent. This is also the case for finger-cuff systems, as recently reported in a meta-analysis [26].…”
Section: All Cardiac Output Monitoring Systems Are Not the Same!mentioning
confidence: 56%
“…While Flotrac™ is reasonably accurate in stable patients, in patients with low SVR, Flotrac™ does not provide accurate CO measurement when compared to invasive CO monitoring [67]. For instance, Murata et al showed that in end-stage liver failure patients, fourth-generation Flotrac™ and PAC readings had poor agreement with each other during liver transplantation [72]. Moreover, Lin et al found that fourth-generation Flotrac™ had a 61.82% and 51.80% error in estimating the CO before and after cardiopulmonary bypass, respectively.…”
Section: Masimo Radical 7 Pulse Co-oximeter™ For Goal-directed Fluid ...mentioning
confidence: 99%